Advances in machine learning for the diagnosis and treatment of stroke. - GAO Xiao-bo; SHU Chang; LI Xiang-fei; LUO Da; GE Le (Chinese Journal of Contemporary Neurology & Neurosurgery, 2023)
With the rapid development of artificial intelligence (AI), machine learning (ML) algorithms has been widely used in stroke diagnosis, treatment and prognosis, and has shown great application potential. This paper summarizes the application status of ML algorithms in stroke research from the aspects of ML algorithms research, ML algorithms in stroke diagnosis and classification diagnosis, outcome prediction, risk factor identification and so on, and looks into the future development direction.